Meningkatkan Hasil Belajar Sistem Pernapasan Manusia Melalui Video Based E-Learning Youtube Siswa Kelas VIII SMP Kartika IV-6 Ambulu Tahun Ajaran 2024/2025 - Viona Rizki Romadona; Waris; Ismul Maulidin Al Habib (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aims to improve student activity and learning outcomes in the human respiratory system through the application of a YouTube-based Video Based Learning (VBL) model. The research method used was Classroom Action Research (CAR), conducted in grade VIII of SMP Kartika IV-6 Ambulu in the 2024/2025 academic year with 18 students. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. Data were collected through observations of student activity and cognitive learning test items. The results showed an increase in both student activity and learning outcomes from cycle I to cycle II. In cycle I, the average student score was 68.72 with a classical completion rate of 44.44%. In cycle II, the average score increased to 85.88 with a classical completion rate of 88.88%. Furthermore, student activity also increased from moderately active to very active. In conclusion, the use of YouTube-based learning videos has proven effective in increasing student motivation, activeness, and learning outcomes in the human respiratory system. Keywords: Student Activities, Learning Outcomes, Video Based Learning, YouTube